David R. Knechtges (trad, y ed.), Wen xuan, or Selections of Refined Literature, Princeton University Press, vol. 1 (1982), pp. ix + 404, vol. 2 (1987), pp. xiv + 627. - Maeth Ch., Russell (Estudios de Asia y África, 1988)
-